2007
DOI: 10.1063/1.2806934
|View full text |Cite
|
Sign up to set email alerts
|

The influence of visible light on transparent zinc tin oxide thin film transistors

Abstract: The characteristics of transparent zinc tin oxide thin film transistors (TTFTs) upon illumination with visible light are reported. Generally, a reversible decrease of threshold voltage Vth, saturation field effect mobility μsat, and an increase of the off current are found. The time scale of the recovery in the dark is governed by the persistent photoconductivity in the semiconductor. Devices with tuned [Zn]:[Sn] ratio show a shift of Vth of less 2V upon illumination at 5mW∕cm2 (brightness >30000cd∕m2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 16 publications
3
106
1
Order By: Relevance
“…12 The trapped charges enhance the TFT conductance and remain for a long period of time leading to a persistent photoconductivity (PPC). G€ orrn et al 13 and Gosain et al…”
mentioning
confidence: 99%
“…12 The trapped charges enhance the TFT conductance and remain for a long period of time leading to a persistent photoconductivity (PPC). G€ orrn et al 13 and Gosain et al…”
mentioning
confidence: 99%
“…In the ionization oxygen vacancy (V O ) model for the LS insta- photo-generated electrons increase the conductivity in the channel [7][8][9]. The enhanced conductivity is known to be persistent because the state transforming from V O 2+ to V O 0 requires a large amount of energy to change the electron configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Although a-IGZO TFTs have such desirable properties, the instability of their threshold voltage (V TH ) under illumination with light can be a critical obstacle for their use in displays because the devices are exposed to ambient light during operation. Recently, several studies have reported on the V TH instability under a negative bias and under illumination stress (NBIS), and the results can be summarized into three models where the degradation is caused by (1) light-induced oxygen interstitial generation [4]; (2) trapping of a photo-generated hole [5,6]; and (3) an ionization oxygen vacancy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The zinc tin oxide (ZTO) film was thought to be an effective active layer for TTFTs because of its wide energy band gap and high resistivity [12][13][14]. We have reported that ZTO TTFTs employing In as source/drain electrodes exhibit a mobility greater than 18.0 cm 2 /Vs [15].…”
Section: Introductionmentioning
confidence: 98%